The potential immunomodulatory role of human milk oligosaccharides in prevention of viral infections and development of asthma in early life - Rijks, Vera; Zuurveld, Marit; Garssen, Johan; Kostadinova, Atanaska I.; Willemsen, Linette E.M. (Frontiers in Immunology, 2025)
Around 10% of the Western population is diagnosed with asthma, and this percentage is only expected to increase in the coming years. Allergic asthma often develops during early infancy and is characterized by chronic pulmonary type 2 inflammation and airway hyperresponsiveness. Severe viral infections in early life are thought to be a risk factor for allergic asthma. The most common causes of severe viral infections in early life are respiratory syncytial virus (RSV) and rhinovirus (RV). How viral infections in early life are related to the later development of asthma is not yet known, but the pathophysiology of RSV/RV infection and asthma overlap in several areas. RSV and RV are both able to induce type 2 immunity which may contribute to the development of allergic asthma which is driven by type 2 responses against airborne allergens such as house dust mites. In early life, infants’ intestines, microbiome and immune function need to mature, and breastfeeding helps to facilitate these major steps in development. Human milk oligosaccharides (HMOs) are the third largest component of human milk and have been shown to promote the development and function of the infant microbiome and may have a beneficial effect on immune maturation by promoting type 1 and regulatory immune responses. In addition, they can stimulate epithelial barrier integrity and directly interact with glycan receptors. Certain bacteria in the gut can metabolize HMOs into short-chain fatty acids (SCFA), which can exert beneficial anti-inflammatory effects locally in the gut or systemically and help maintain barrier properties and immune homeostasis. HMOs and SCFA could have protective effects on both the immune pathways in allergic asthma and viral infections. This review describes the molecular and immunomodulatory mechanisms by which different HMOs and SCFA may help defend against viral infections and also protect against allergic asthma.